2019
DOI: 10.1108/jsit-10-2018-0137
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the adoption of cloud of things

Abstract: Purpose The purpose of this study is to determine the significant factors affecting the adoption of Cloud of Things (CoT) by Indian small and medium-sized enterprises, using exploratory and confirmatory factor analysis. Design/methodology/approach Significant factors that impact CoT implementation were identified through a detailed literature survey. A conceptual framework and hypotheses were proposed for linking the significant factors so identified, namely, cost saving, relative advantage, sharing and coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…There have been numerous CC adoption studies that are conducted in the Indian context (Sharma and Sehrawat, 2020b). The studies cover aspects such as automation of automobile manufacturing (Singh and Misra, 2019), legal entanglements (Patnaik and Dash, 2021), academic performance (Sharma et al , 2020b), IT performance (Gangwar et al , 2015), semiconductor performance (Rahi et al , 2017), SME performance (Narwane et al , 2019, 2020), and health-care facility (Sharma and Sehrawat, 2020a). The authors have also used various adoption frameworks such as TAM-TOE (Gangwar et al , 2015), TAM-TOE-risk model (Raut et al , 2018b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been numerous CC adoption studies that are conducted in the Indian context (Sharma and Sehrawat, 2020b). The studies cover aspects such as automation of automobile manufacturing (Singh and Misra, 2019), legal entanglements (Patnaik and Dash, 2021), academic performance (Sharma et al , 2020b), IT performance (Gangwar et al , 2015), semiconductor performance (Rahi et al , 2017), SME performance (Narwane et al , 2019, 2020), and health-care facility (Sharma and Sehrawat, 2020a). The authors have also used various adoption frameworks such as TAM-TOE (Gangwar et al , 2015), TAM-TOE-risk model (Raut et al , 2018b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relative advantage is the degree to which an innovation is preferred to the concept it replaces (Rogers, 1995;Panchal and Krishnamoorthy, 2019). In this research, relative advantages rest in asset management to determine whether innovative security solutions are more appropriate in HEIs than the outdated technology they intend to replace (Gangwar 2018; Narwane et al, 2019;Pan & Pan, 2019). It looks at the benefits of new technology in HEIs compared to security technologies already in use.…”
Section: Technological Contextmentioning
confidence: 99%
“…Top management's role is significant not only in acquiring connectivity, information sharing but also on resource bundling and BDA process assimilation (Gunasekaran et al, 2017). Narwane et al (2019a) investigated the adoption of the Cloud of Things (integration of cloud computing and the IoT) for SMEs. The study found the positive influence of collaboration, relative advantage and cost-saving on the Cloud of Things.…”
Section: Imds 1219mentioning
confidence: 99%